A COMPARATIVE ANALYSIS OF “HIBBAT UL-HAQOYIQ” AND “QUTADGHU BILIG” (Multidisciplinary Journal of Science and Technology, 2025)
Annotation. This article provides a comparative analysis of Ahmad Yugnaki’s Hibbat ul-haqoyiq and Yusuf Khass Hajib’s Qutadghu Bilig, focusing on their philosophical, ethical, and literary connections. Both works are considered major sources of moral and didactic thought in Turkic literature. Employing comparative, historical, and philosophical methods, the study reveals their common and distinct aspects based on the ideas of knowledge, justice, and perfection. The findings shed light on the evolution of didactic thinking in Turkic literature.